Analysis of Differences in Employee Performance on Job Satisfaction in the Company Hutama Karya Infrastructure Zone 4 Langkat Regency - Rahmat Akbar; Gerry Silaban; Umi Salmah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Employee performance measures the success of an employee's achievement in carrying out his duties and responsibilities in a company or organization. This study aimed to analyze the effect of individual characteristics and job satisfaction on the performance of employees of the Hutama Karya Infrastructure Company Zone 4 Langkat Regency. This type of research is quantitative research with a cross-sectional design. The research location was conducted at the Hutama Karya Infrastructure Company Zone 4 Langkat Regency, and the research was conducted from August to November 2023. The study population was all employees at the Hutama Karya Infrastruktur Zone 4 Langkat Regency Company, which amounted to 70 employees. The sampling technique used in the study was total sampling, so the number of samples in this study was 70 employees. The data collection technique used a questionnaire method. The data analysis method used is statistical testing using the chi-square test. The results showed that there was an influence of individual characteristics on length of service (p-value=0.002), education (p-value=0.025), age (p-value=0.001), no influence of gender (p-value=0.708), marital status (p-value=0.726). There was a relationship between job satisfaction (p-value=0.023) with employee performance at the Hutama Karya Infrastructure Company Zone 4 Langkat Regency. It is recommended that leaders provide direction and guidance for new employees in carrying out their work, and for employees, it is hoped that new employees will follow directions at work and for all employees to carry out study assignments and attend training so that they have good abilities at work. Keywords: Characteristics, Employee, Job satisfaction, Performance